ERGO1: novo protótipo para condicionamento físico de cadeirantes e paratletas - Vieira, Sérgio Augusto Albino (2012)
Physical activity is one of the ways to promote health and social integration of disabled persons. Recently, some actions by the federal government search to guarantee the full exercise of individual rights. Sports are a great way to promote social integration and Brazil has shown a crescent performance in the Paralympics. To evaluate the physical conditioning, ergometers are used. However, these equipments are derived from tests that already exist for able-bodied persons and, normally, don’t perfectly adapt to the motor gesture naturally executed by disabled people, which is the propulsion of the wheelchair through the application of a force on the propulsion rims. According to this, the objective of this work is to develop a new prototype of a wheelchair ergometer that respects the specificity of movements and allows the physical evaluation of disabled persons. This new prototype is called ERGO1 and it’s an evolution of the previous one, ERG-CR09, with a new structure that is lighter and smaller. Resistance generation was made through an electromagnetic brake similar to the previous one, but positioned under the seat. An application developed in LabVIEW language is responsible for controlling the electronic part of the prototype, configuring the load that is going to be used and making the acquisition of the rotation and torque signals from the system so the power, energy and fatigue of the user may be estimated. Definition of load level is made through an weight acquisition automatic system positioned in the seat structure. Besides Wingate protocol, a new test, called incremental protocol was implemented. Through initial tests was observed that the variation of resistance levels allows the evaluation of physical conditioning for both protocols. Also, fatigue levels characterized in the literature were observed. This happened for the fatigue based on power levels and in those based on the equivalent energy. Another important innovation of this prototype comes from the power signals acquired that had its peaks smoothed by inertial flywheels.